2011
DOI: 10.1007/s10517-011-1180-8
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Expression of Brain-Derived Neurotrophic Factor at the Site of Implantation of Allogenic and Xenogenic Neural Stem (Progenitor) Cells in Rats with Ischemic Cortical Stroke

Abstract: Ischemic stroke was modeled in the sensorimotor zone of the brain cortex in adult rats. Rat embryonic nervous tissue, neural stem cells from human olfactory epithelium, and rat fibroblasts (cell control) were implanted into the peri-infarction area of rats of different groups immediately after stroke modeling. Expression of BDNF mRNA was analyzed 7 days after surgery by real-time PCR. BDNF expression in cell preparation before their implantation was minimum. The expression of BDNF mRNA increased by 5-6 times i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Experiments have demonstrated that transplanted NSCs exhibit strong plasticity, can easily integrate with host cells and can establish a stable synaptic connection and become functional substituting nerve cells [26-28]. Additionally, NSCs may produce neurotrophic factors that facilitate the recovery of impaired tissues in the diseased brain region [29-32]. Consistent with these findings, we found that autologous NSC-like cells derived from MSCs could differentiate into neuronal and glial lineages in vitro.…”
Section: Discussionsupporting
confidence: 82%
“…Experiments have demonstrated that transplanted NSCs exhibit strong plasticity, can easily integrate with host cells and can establish a stable synaptic connection and become functional substituting nerve cells [26-28]. Additionally, NSCs may produce neurotrophic factors that facilitate the recovery of impaired tissues in the diseased brain region [29-32]. Consistent with these findings, we found that autologous NSC-like cells derived from MSCs could differentiate into neuronal and glial lineages in vitro.…”
Section: Discussionsupporting
confidence: 82%
“…Lim et al, 2011;Ma et al, 2012;Makar et al, 2008;Makar et al, 2009). Furthermore, modest endogenous levels of BDNF protein in mesenchymal and neural stem cells (Chekhonin et al, 2011;Li et al, 2006;Mauri et al, 2012) have also been shown to be beneficial on co-cultured neurons (Mauri et al, 2012). Hence, the 8-fold overexpression of functional BDNF-GFP we achieved here is of physiological relevance.…”
Section: Expression Level Of Bdnf-gfp In Escsmentioning
confidence: 67%
“…First, MSCs could significantly integrate with neural host cells, establish synaptic connections, and recover nerve cell functions (24)(25)(26). In addition, MSCs could produce some neurotrophic factors facilitating recovery of disturbed neuronal tissues in affected regions (27)(28)(29)(30). In fact, different types of stem cells, such as MSCs, could differentiate into neuronal and glial lineages.…”
Section: Discussionmentioning
confidence: 99%